Brand admiration - Park, C. Whan (Wiley, 2016)
Brand Admiration uses deep research on consumer psychology, marketing, consumer engagement and communication to develop a powerful, integrated perspective and innovative approach to brand management. Using numerous real-world examples and backed by research from top notch academics, this book describes how companies can turn a product, service, corporate, person or place brand into one that customers love, trust and respect; in short, how to make a brand admired. The result? Greater brand loyalty, stronger brand advocacy, and higher brand equity. Admired brands grow more revenue in a more efficient way over a longer period of time and with more opportunities for growth